Supershed Escherichia coli O157:H7 Has Potential for Increased Persistence on the Rectoanal Junction Squamous Epithelial Cells and Antibiotic Resistance. (14th April 2020) - Mir, Raies A.; Brunelle, Brian W.; Alt, David P.; Arthur, Terrance M.; Kudva, Indira T
Abstract : Supershedding cattle shed Escherichia coli O157:H7 (O157) at ≥ 10 4 colony-forming units/g feces. We recently demonstrated that a supershed O157 (SS-O157) strain, SS-17, hyperadheres to the rectoanal junction (RAJ) squamous epithelial (RSE) cells which may contribute to SS-O157 persistence at this site in greater numbers, thereby increasing the fecal O157 load characterizing the supershedding phenomenon. In order to verify if this would be the signature adherence profile of any SS-O157, we tested additional SS-O157 isolates ( n = 101; each from a different animal) in the RSE cell adherence assay. Similar to SS-17, all 101 SS-O157 exhibited aggregative adherence on RSE cells, with 56% attaching strongly (>10 bacteria/cell; hyperadherent) and 44% attaching moderately (1–10 bacteria/cells). Strain typing using Polymorphic Amplified Typing Sequences (PATS) analysis assigned the 101 SS-O157 into 5 major clades but not to any predominant genotype. Interestingly, 69% of SS-O157 isolates were identical to human O157 outbreak strains based on pulsed field gel electrophoresis profiles (CDC PulseNet Database), grouped into two clades by PATS distinguishing them from remaining SS-O157, and were hyperadherent on RSE cells. A subset of SS-O157 isolates ( n = 53) representing different PATS and RSE cell adherence profiles were analyzed for antibiotic resistance (AR). Several SS-O157 (30/53) showed resistance to sulfisoxazole, and one isolate was resistant to both sulfisoxazole and tetracycline. Minimum inhibitory concentration (MIC) tests confirmed some of the resistance observed using the Kirby–Bauer disk diffusion test. Each SS-O157 isolate carried at least 10 genes associated with AR. However, genes directly associated with AR were rarely amplified: aac (3)-IV in 2 isolates, sul 2 in 3 isolates, and tetB in one isolate. The integrase gene, int, linked with integron-based AR acquisition/transmission, was identified in 92% of SS-O157 isolates. Our results indicate that SS-O157 isolates could potentially persist longer at the bovine RAJ but exhibit limited resistance towards clinical antibiotics.